CURRICULAR STRATEGIES FOR THE STRENGTHENING OF ZENU ETNOIDENTITY IN THE ARENA TECHNICAL AGRICULTURAL EDUCATION INSTITUTION - Salazar, Lucy (Revista Arbitrada Formación Gerencial, 2022)
The central axis of this study is to understand the curricular strategies applied by teachers for the strengthening of Zenu Ethnoidentity in La Arena Agricultural Technical Educational Institution. Which focuses on a qualitative perspective that emphasizes the rescue of the subject, the profound nature of reality and its environment as a dynamic structure, at the level of sustenance the same is supported by the foundations of multiple authors such as Cerda (2002). ) Méndez (2006), Tamayo and Tamayo (2012), Sichray and Pari (2003), López (2004). From the perspective of qualitative research, the development of the study is in line with the ethnographic method. The information was collected through direct observation techniques and qualitative interviews. For the purposes of the sample, six (6) subjects of the management staff and professors of La Arena Agricultural Technical Educational Institution were taken. The reliability of said population is relative since it is replicable, as will ethics as a preponderant condition. Also by way of findings it was possible to know that today in terms of the Zenú Ethnoidentity in La Arena Agricultural Technical Educational Institution is less the discrimination suffered, however, we must still work on avoiding xenophobia, which rather promote your contribution to the Colombian society, where people of different ages, traditions, sectors, cultures and disciplines of knowledge participate accordingly. Similarly, it was evident that the ideological level, where cultural domination is rooted, is often expressed in attitudes of rejection of this population by some sectors of the non-indigenous population, so their culture is seen as unusual forms of  lifetime.